1985
DOI: 10.1016/0014-5793(85)80798-5
|View full text |Cite
|
Sign up to set email alerts
|

Human Z α1‐antitrypsin accumulates intracellularly and stimulates lysosomal activity when synthesised in the Xenopus oocyte

Abstract: Microinjection of human liver mRNA from a patient homozygous for α1‐antitrypsin deficiency (PiZZ) into Xenopus oocytes led to a 2–10‐fold increase in lysosomal activity. Stimulation of lysosomal activity was not observed when mRNA from a normal human liver (α1‐antitrypsin PiMM), or water was injected into the oocyte. This lysosomal activity was oocyte derived and was not due to translation products of the human liver mRNA. Thus a protein that accumulates intracellularly in the secretory pathway is capable of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Studies using mRNA isolated from normal (MM) and deficient (ZZ) livers showed both messages were equivalent in stability and in their translation and subsequent glycosylation in cell-free systems (32)(33)(34). Injection ofthe normal M and variant Z RNA into a surrogate cell, the toad oocyte, confirmed that there was equivalent initial synthesis of the two polypeptides but showed that, whereas all the M protein was secreted, only a fraction ofthe Z antitrypsin was secreted, most ofthe Z product being blocked within the oocyte at the final (high mannose) stage of processing (35)(36)(37)(38). This accumulation of the abnormal antitrypsin was accompanied by a burst of lysosomal activity in the oocyte, indicating that the blockage of the Z antitrypsin was accompanied by increased proteolytic degradation (36).…”
Section: Molecular Pathology Ofthe S and Z Variantsmentioning
confidence: 99%
“…Studies using mRNA isolated from normal (MM) and deficient (ZZ) livers showed both messages were equivalent in stability and in their translation and subsequent glycosylation in cell-free systems (32)(33)(34). Injection ofthe normal M and variant Z RNA into a surrogate cell, the toad oocyte, confirmed that there was equivalent initial synthesis of the two polypeptides but showed that, whereas all the M protein was secreted, only a fraction ofthe Z antitrypsin was secreted, most ofthe Z product being blocked within the oocyte at the final (high mannose) stage of processing (35)(36)(37)(38). This accumulation of the abnormal antitrypsin was accompanied by a burst of lysosomal activity in the oocyte, indicating that the blockage of the Z antitrypsin was accompanied by increased proteolytic degradation (36).…”
Section: Molecular Pathology Ofthe S and Z Variantsmentioning
confidence: 99%
“…Indeed, through the use of inhibitors capable of selectively, and independently, targeting the proteasomal or lysosomal pathways, it has been demonstrated in somatic systems that proteins bearing more extensive modifications are preferentially directed away from the proteasome and toward lysosomal degradation pathways whereupon they are recycled via the action of acidic lysosomal hydrolases [ 190 ]. This pathway has been demonstrated in Xenopus oocytes wherein lysosomal activity was stimulated upon intracellular accumulation of damaged proteins [ 191 ].…”
Section: Increased Vulnerability Of the Ageing Oocyte To Oxidativementioning
confidence: 99%
“…In one report, accumulation of @,-AT Z in Xenupus oocytes was associated with an increase in release of lysosomal enzymes. 90 Several recent studies in model systems have provided interesting and, perhaps, relevant information. Raposo er al.…”
Section: Mechanism Of Liver Cell Injurymentioning
confidence: 99%